S67 Mortality in copd patients following community acquired pneumonia: a population database analysis of linked healthcare records. (15th November 2016) - Williams, N; Coombs, NA; Johnson, M; Josephs, L; Rigge, LA; Thomas, DM; Wilkinson, TMA
Abstract : Introduction: Community acquired pneumonia (CAP) is a common occurrence in patients with chronic obstructive pulmonary disease (COPD), yet controversy still remains about its affect on outcome. We therefore investigated the impact of CAP on mortality in a cohort of COPD patients identified from the Hampshire Health Record analytical database, a local NHS database containing linked, anonymised primary and secondary care records. Methods: Patients were defined as having COPD if they had a diagnostic Read code in their primary care record at any time prior to the 1 st January 2010 and were aged ≥40 years at the start of the study. CAP episodes occurring over a 5-year period from 1 st January 2010 were identified using Read and ICD-10 codes. The outcome measure was all-cause mortality following a CAP diagnosis. Cox proportional hazard modelling was used to estimate hazard ratios (HR) and confidence intervals (CI), adjusting for age, sex, GOLD stage, smoking status and inhaled corticosteroid use (ICS)). Results: The cohort comprised 14506 COPD patients. The mean age was 70.3 (±10.8) years and 53.6% were male. 1931 (13.3%) patients had at least one CAP and 2870 (19.8%) deaths occurred over the study period. 28.2% of patients diagnosed with CAP died compared to only 9.7% of those without a CAP diagnosis (p < 0.001). Logistic regression analysis, controlling for potential confounders identified CAP as an independent risk factor for future mortality (odds ratio 2.72; CI 2.37–3.12, p < 0.001). Compared to younger individuals (40–59 years) those aged 60–79 and >80 years had the highest mortality risk following CAP (HR 2.65; CI 1.61–4.34, HR 7.03; CI 4.27–11.57 respectively, both p < 0.001). Concurrent use of inhaled Fluticasone or Budesonide were associated with reduced mortality risk following CAP (HR 0.82; CI: 0.68–0.98 p = 0.029, HR 0.55; CI: 0.39–0.76 p < 0.001, respectively) (Figure 1 ). Conclusion: CAP in COPD is associated with increased risk of mortality, especially in older individuals. Although known to increase CAP risk, ICS use appears to reduce risk of mortality following CAP. Further research to understand the mechanisms underlying CAP risk in COPD and modulating effects of ICS is key, to guide development of future, targeted preventative strategies.